(untitled) (Chest & Heart Journal, 2021)
Diffusing capacity of lung for carbon monoxide (DLCO), also known as transfer factor of the lung for carbon monoxide (TLCO)1, is a measurement to assess the ability of the lungs to transfer gas from inspired air to the bloodstream 2. In the United States, the test is known as the DLCO and the units of measure are mL/min/mm Hg. DLCO is indicated in the evaluation of parenchymal and non-parenchymal lung diseases in conjunction with spirometry. A DLCO of less than 60% predicted portends a poor prognosis for lung cancer resection. Inability to follow instructions is a contraindication to a DLCO test (CPT code 94729). In the single breath method, the patients are asked to take normal resting breaths initially; this is followed by full exhalation up to residual volume (RV), after which the patient is asked to rapidly inhale the test gas up to vital capacity (VC). Anemia can reduce DLCO. Hence DLCO is adjusted for hemoglobin values. KCO is CO transfer coefficient, usually written as DLCO/Va, which indicates the efficiency of CO transfer by alveoli. High KCO occur in extra-parenchymal restriction and in “Extra-Hb”. Low DLCO and Low KCO is seen in COPD with emphysema due to alveolar destruction. Decreased DLCO seen in obstructive lung diseases, cardiovascular diseases also in systemic disease involving lungs. Causes of increased DLCO includes polycythemia , obesity, asthma, which are characterized by large lung volumes.11 High DLCO also seen in pulmonary hemorrhage. A normal DLCO with a restrictive pattern on PFT suggests neuromuscular or chest wall disorder. Chest Heart J. 2020; 44(1) : 43-47